An uncommon complication of Listeria monocytogenes infection: Polyradiculoneuritis following Listeria meningoencephalitis - Tebib, N. (IDCases, 2018)
Listeria monocytogenes, primarily a foodborne pathogen, is commonly responsible for disorders affecting the central nervous system and cranial nerves. We hereby present the first case to our knowledge of listeriosis linked to a peripheral neurological disorder causing acute upper limb weakness.